Pengaruh Media Sosial Tiktok Terhadap Perilaku Konsumsi Mahasiwa Ilmu Komunikasi Universitas Medan Area - Balga, Nakata; Khairullah, Khairullah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
TikTok is a new social media platform that allows users to express themselves and hone their talents through video content. By creating engaging videos, they can also interact in the comments section and private chat. The purpose of this study is to analyze the influence of TikTok on the consumer behavior of students at Medan Area University. This thesis employed qualitative research methods. Quantitative research methods are used to conduct research in a naturalistic manner using various available methods. The results show that the value of F count F table (4.316 2.0), thus the hypothesis is accepted, so it can be concluded that TikTok Social Media has a Positive Influence on the Consumptive Behavior of Medan Area University Students. So it can be concluded that the null hypothesis H0 is rejected and Ha is accepted, which means there is an influence between the TikTok social media variable (X) on the consumptive behavior variable of Medan Area University Communication students. (Y) .